Efeito da curcumina e vimblastina nas vias de sinalização celular e estresse oxidativo em cultura de células de melanoma humano - Lunkes, Vinícius Leobet (2021)
Cancer is a leading cause of death in dogs and cats. Melanoma skin cancer originates from melanocytes and is more severe due to the possibility of metastases and a wide variety of presentations. Treatment involves chemotherapy, such as vinblastine, but it can be hampered by low responsiveness and adverse effects. Curcumin, a substance extracted from the rhizomes of the Curcuma longa plant, has antineoplastic effects, inhibiting tumor initiation and tumor progression, as it acts on a wide variety of genes, growth factors and enzymes that regulate cell proliferation and apoptosis. Considering the beneficial effects of curcumin in various diseases, its effects have been widely studied. Therefore, the objective of this work was to evaluate the effect of curcumin addition in human melanoma cell cultures on oxidative stress markers, antioxidant enzyme activity, purinergic system components, cell migration, apoptosis and cell cycle. For this, human melanoma cells of the SK-MEL-28 lineage were treated for 24 hours with curcumin in increasing concentrations, in order to define the concentration capable of inhibiting 50% of cell cultures, which will be used in the other assays. Next, cell signaling pathways, such as the oxidative mechanism and the purinergic system, as well as cellular effects, such as apoptosis and cell cycle, were evaluated. Concomitantly, the trials were performed using vinblastine (alone or associated with curcumin), in order to compare the results with a substance used in melanoma chemotherapy. After an incubation period of 24 hours, the concentration of 40 μM of curcumin inhibited 50% of cell cultures, and was used in the other assays. Curcumin inhibited cell migration and caused the arrest of cell replication, inducing cells to die by apoptosis. Curcumin also disrupted the cascade that culminates in the production of adenosine, inhibiting immunosuppression in tumor cells, and causing an increase in the production of reactive oxygen species. Vinblastine, in turn, reduced the activity of the adenosine deaminase enzyme and increased the production of reactive oxygen species, promoting cell apoptosis. It can be concluded that curcumin has a pro-oxidative effect on tumor cells, modulates the immune response and causes apoptosis and cell cycle arrest in human melanoma cell cultures, which could be a promising substance in the conventional treatment of melanoma.